Cuidado ao paciente na terminalidade: vivência de profissionais da saúde de um serviço de atenção domiciliar - Platel, Indiara Carvalho Dos Santos (2016)
The caring is a action endowed with responsibility, in which we shall consider the different dimensions and real necessities of the human being. It is a peculiar characteristic to all the health professionals, which demand fundamental practices at the life quality and promotion, mainly considering the terminal ill assistance. This study aimed to investigate the health professional experience at a household attention service with the care turned to the terminal patient. Methodology: It is an exploratory-qualitative research, guided by criteria established at the Qualitative Research Reporting. The scenario involved the Household attention service, located in João Pessoa – PB. Twenty professionals from the superior level participated at this study: two doctors, six nurses, Five physiotherapists, two nutritionists, two psychologist, two speech therapist and a social assistant from the multi professionals team at the household attention and from the multi professional support teams. To capture the empirical material, was used the interview technique that followed a script containing guided questions, pertinent to the proposed objective to this study. Data were collected between February and May 2015, after the agreement of the Education Management at Health from the referred city and the Ethics Research Committee of the Health Sciences Center approval, as certificate as CAAE register under the number: 39989514.0.0000.5188. The empirical material was analyzed in a qualitative way, through the Content Analysis Technique proposed by Bardin. . Results: From data collection, emerged two originals manuscripts. To the first was given the name “Professional experience at a household attention service at the terminal patient caring”, from with were identified three categories: “Humanization at the terminal patient assistance: promoting autonomy, dignity and life quality”; “The terminal patient: feelings experienced during the caring promotion”; and “Terminal patient care, personal and professional permanent learning.” And the second, “Therapeutic actions promoted to the terminal patient: professionals experience at a household attention service, which resulted in two categories construction: “Therapeutic actions directed to biological necessities of the terminal ill to comfort and life quality promotion.” And “Therapeutic actions promoted to answer the psycho socials and spirituals terminal patient’s needs” Conclusion: The health professionals experience during the terminal patient caring action, in the household context, is based on a holistic assistance, with Essentials therapeutic to the humanized care, that brings respect and dignity to the patient at the life ending process.